Cars, roads and middle classes in the 1920s. In between the Cuzco icon and the national tourism development - Armas Asín, Fernando (2017)
This study analyses the history of Peruvian tourism in the decade of 1920: Its development on the Andean south region based on receptive tourism, as well as the private companies actions and the regional elites. It holds that National tourism developed from the work of Touring Club Peruano and the road works undertaken during the government of President A.B. Leguía. Lastly, it proposes that it is in this decade that the first public policies related to tourism can be verified.